Comparative study on milk compositions of cattle, sheep and goats in Nigeria - Malau-Aduli , A.E.O.; Anlade, Y.R. (2002)
Variations in the milk composition of Nigerian cattle, sheep and goats as well as residual phenotypic correlations between the milk constituents were investigated. The study utilized Bunaji, Yankasa and Red Sokoto breeds of cattle, sheep and goats, respect ively. Results indicated that sheep and goats differed significantly (P<0.05) from cattle in all constituents except protein percentage that averaged 5.43, 5.43 and 5.49%. Caprine milk contained the highest percentages of fat (5.80%), total solids (15.37%) and ash (0.77%), while bovine milk contained the least percentages of fat (0.68%) and lactose (1.84%). Overall, milk compositions of sheep and goats were very similar since they were not statistically different from each other (P>0.05). Residual phenotypi c correlations between the milk constituents revealed highly significant (P<0.01) and positive relationships between total solids and solids -not-fat (0.97 and 0.98 in cattle and sheep, respectively). All other correlations were positive (ranging from 0.12 to 0.77), except between protein and total solids (-0.44) and protein and solids-not-fat (-0.64) in cattle. Multiple linear regression equations were fitted to predict the percentages of protein and fat. It was demonstrated that protein percentage could be predicted from total solids and solids -not-fat with the highest accuracy of 94, 86 and 82 % in cattle, sheep and goats, respectively. On the other hand, the accuracy of prediction of fat percentage was very low in all the species (R 2=0.01, 0.03 and 0.37 in cattle, sheep and goats, respectively) .